2014
DOI: 10.1177/2150135114537313
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Drainage Versus Pleural Drainage After Pediatric Cardiac Surgery

Abstract: Background: We aimed to determine whether infants undergoing cardiac surgery would more efficiently attain negative fluid balance postoperatively with passive peritoneal drainage as compared to traditional pleural drainage. Methods: A prospective, randomized study including children undergoing repair of tetralogy of Fallot (TOF) or atrioventricular septal defect (AVSD) was completed between September 2011 and June 2013. Patients were randomized to intraoperative placement of peritoneal catheter or right pleura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…5,6 A study of patients with atrioventricular septal defect (AVSD) or tetralogy of Fallot (TOF) showed that AVSD patients with peritoneal catheters achieved a negative fluid balance significantly faster than those without. 7 In contrast, no significant differences were observed in TOF patients. 7 These results suggest that the benefit of a peritoneal catheter may not be universal but dependent on patients' underlying physiology.…”
Section: Commentmentioning
confidence: 91%
See 2 more Smart Citations
“…5,6 A study of patients with atrioventricular septal defect (AVSD) or tetralogy of Fallot (TOF) showed that AVSD patients with peritoneal catheters achieved a negative fluid balance significantly faster than those without. 7 In contrast, no significant differences were observed in TOF patients. 7 These results suggest that the benefit of a peritoneal catheter may not be universal but dependent on patients' underlying physiology.…”
Section: Commentmentioning
confidence: 91%
“…7 In contrast, no significant differences were observed in TOF patients. 7 These results suggest that the benefit of a peritoneal catheter may not be universal but dependent on patients' underlying physiology. One patient in that study required surgical revision because of a small colonic perforation by the peritoneal catheter, which prolonged hospital stay.…”
Section: Commentmentioning
confidence: 91%
See 1 more Smart Citation
“…Retrospective studies in children recovering from selected cardiac operations have found an association between peritoneal drainage and shorter time to negative fluid balance and extubation (48,60,61). Intraoperative or early postoperative placement of a peritoneal drain may be more prudent than awaiting the development of renal failure (62,63).…”
Section: S39mentioning
confidence: 98%
“…We completed full-text review of 17 studies (13-29), including 4 RCTs (17,20,25,26) (29). Eleven studies were from North America (14,16,17,(19)(20)(21)(23)(24)(25)(26)(27), three from Europe (13,15,28), and three from Asia (18,22,29).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%